Homeschooling in a Society of Change - Cieśleńska, Beata; Szempruch, Jolanta; Smyła, Joanna (Wydawnictwo Uniwersytetu Jana Kochanowskiego w Kielcach, 2023)
The aim of the article is to present the phenomenon of homeschooling in the changing social reality, which is not a completely new form of education, but is considered a novelty in the education of children and youth. The article uses historical and pedagogical analysis of sources, using min. legal acts, analyzed documentation reflecting the activities of home education in the country. It presents the School in the Cloud, created for the needs of alternative education, the popularity of which proves the need for innovation in education. It focuses on showing alternative education as a trend in modern society and the legal and systemic conditions that govern this process. It draws attention to models of homeschooling in countries with the greatest freedom in education policy – the USA and Great Britain. It shows the motives for the choice of home education and the process of socialization related to this form of education, paying attention to the fact that the belief about socialization deficiencies is only a false idea of the education process at home. It emphasizes the need for changes in education for the future, paying attention to the flexibility of the concept of education, openness to new, alternative forms that are not included in the schemes and do not captivate with mandatory content. In conclusion, it draws attention to institutionalism, which is no longer the dominant form of education today.